An introduction to the Gospels and Acts - Myers, Alicia D. (Essentials of biblical studies, 2022)
Introduction : reading the Gospels and Acts in context -- Mark's story : the gospel in Roman Palestine -- Matthew's story : the gospel in Jewish contexts -- Luke's story, part 1 : the gospel as a message of inclusion -- Luke's story, part 2 : God's spirit-driven mission in the book of Acts -- John's story : recognizing the incarnate Word -- Apocryphal Gospels and Acts : stories beyond the New Testament -- Conclusion : reading the Gospels and Acts today.